Zwitterionic gel electrolyte and preparation method thereof
Through the preparation method of zwitterionic gel electrolyte, the network structure of sulfobetaine and acrylic acid and the second network of polymer polymers are used, combined with the treatment of ionic solution and potassium hydroxide solution, the problems of poor conductivity and mechanical strength of gel polymer electrolyte are solved, and a high-performance zinc-air battery electrolyte is achieved.
Patent Information
- Application Number
- CN202411993815.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing gel polymer electrolytes have poor electrical conductivity and mechanical strength, which limits the widespread use of zinc-empty batteries.
Using the preparation method of zwitterionic gel electrolyte, a network structure is formed by free radical in situ polymerization of sulfobetaine and acrylic acid, and a polymer as the second network is used to combine the treatment of ionic solution and potassium hydroxide solution to enhance the mechanical strength and electrical conductivity of the gel.
It realizes a high-performance zwitterion-based gel electrolyte, with an ionic conductivity of 250~310mS/cm and a tensile strength of 20~50kPa. It is suitable for zinc-empty batteries, with an open circuit voltage between 1.40~1.43V.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer and energy storage, and relates to a zwitterion-based gel electrolyte and a preparation method thereof. Background Art
[0002] With the rapid development of society and the continuous deepening of infrastructure construction, the demand for fossil energy consumption such as coal, oil, and natural gas is also growing. As a result, the over-exploitation and deep dependence on fossil energy have put the natural and ecological environment under tremendous pollution pressure. Therefore, it is particularly important to develop a new generation of green chemical clean energy. Flexible batteries have attracted widespread attention due to their excellent performance in the storage and conversion of chemical energy. It is also because of their controllable size and good flexibility that they have become an indispensable part of portable wearable devices. At present, the power of portable electronic devices mainly comes from non-flexible lithium-ion batteries. However, it is difficult to meet the requirements of digital textiles for energy storage devices such as safety, comfort, small size, high capacity, and environmental protection. Zinc-air batteries have many advantages such as high theoretical energy density, good safety, low cost, environmental friendliness, and repeated charge and discharge. They are one of the ideal choices for designing wearable flexible power sources. A key issue in flexible zinc-air batteries is the need to use solid electrolytes to replace traditional liquid electrolytes. Therefore, it is necessary to develop advanced solid electrolyte systems to meet the needs of battery charging and discharging processes, which plays a vital role in the performance of zinc-air batteries.
[0003] Gel polymer electrolytes need to have high ionic conductivity, excellent flexibility, and good interfacial compatibility with electrodes. The use of this type of electrolyte makes it possible to develop high-performance flexible solid-state zinc-air batteries. However, the conductivity and mechanical strength of existing gel polymer electrolytes are poor, which seriously limits the widespread use of zinc-air batteries. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a zwitterion-based gel electrolyte and a preparation method thereof, thereby solving the technical problems of poor conductivity and mechanical strength of the gel polymer electrolyte in the prior art.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a zwitterion-based gel electrolyte comprises the following steps: S1: dissolving acrylic acid and sulfobetaine in an aqueous solution of a high molecular weight polymer, and stirring to obtain a monomer mixture; the high molecular weight polymer is at least one of polyvinyl alcohol, polyacrylamide and sodium polyacrylate; S2: adding NN methylenebisacrylamide to the monomer mixture, stirring evenly, adding an initiator, continuing to stir for reaction, and then thermally polymerizing the product to obtain a zwitterionic gel; S3: After the zwitterion gel is immersed in an ion solution, the product is placed in a potassium hydroxide solution for swelling treatment to obtain the zwitterion-based gel electrolyte; the ion solution is at least one of zinc sulfate solution, sodium sulfate and sodium citrate.
[0006] Preferably, the ratio of acrylic acid, sulfobetaine and high molecular polymer is (1-3) mL: (0.1-2) g: (0.1-1) g.
[0007] Preferably, the preparation process of the aqueous solution of the polymer is: adding 0.1-1 g of the polymer into 10-50 mL of water, and then stirring at 50-100° C. to dissolve it, to obtain the aqueous solution of the polymer.
[0008] Preferably, the ratio of acrylic acid, sulfobetaine, NN methylenebisacrylamide and initiator is (1-3) mL: (0.1-2) g: (0.01-0.05) g: (0.01-0.1) g.
[0009] Preferably, NN methylenebisacrylamide is added to the monomer mixture, stirred for 1 to 2 hours, and then an initiator is added, and stirring is continued for 10 to 60 minutes.
[0010] Preferably, during the thermal polymerization process, the temperature is 40-60° C. and the time is 3-6 h.
[0011] Preferably, the concentration of the ionic solution is 0.1-3 M, and the zwitterionic gel is immersed in the ionic solution for 1-2 days.
[0012] Preferably, the concentration of the potassium hydroxide solution is 3-6 M, and the swelling treatment time is 1-2 days.
[0013] A zwitterion-based gel electrolyte is prepared by the above method; the zwitterion-based gel electrolyte has an ion conductivity of 250-310 mS / cm and a tensile strength of 20-50 kPa.
[0014] A zinc-air battery comprises the above-mentioned zwitterion-based gel electrolyte; the open circuit voltage of the zinc-air battery is 1.40-1.43V.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a preparation method of a zwitterion-based gel electrolyte. The preparation method uses sulfobetaine, acrylic acid, and a high molecular polymer as raw materials. Based on the action of an initiator, a free radical in-situ polymerization reaction of sulfobetaine and acrylic acid monomer is initiated to form a sulfobetaine / acrylic acid network as a first skeleton, and the high molecular polymer is used as a rigid second network to form a second skeleton. The gel is then immersed in an ionic solution, and the ionic solution includes cations and anions, wherein the cations can be cross-linked with the gel to improve the mechanical strength of the gel, and the anions cause the PVA chains to precipitate through the Hofmeister effect, further improving the mechanical strength of the gel, that is, the Hofmeister effect is used to enhance the conductivity and mechanical strength of the gel, and finally a double network gel electrolyte is formed. In the double network gel electrolyte, the quaternary ammonium group of sulfobetaine and the carboxylic acid group of acrylic acid form an efficient ion migration channel, thereby improving the conductivity, and the high sensitivity of polyvinyl alcohol to the Hofmeister effect of the sulfate group enhances the mechanical strength of the gel. The obtained gel electrolyte has a honeycomb pore structure, can absorb a large amount of electrolyte solution, and has excellent hydration.
[0016] Furthermore, the ratio of acrylic acid, sulfobetaine and high molecular polymer is (1-3) mL: (0.1-2) g: (0.1-1) g, which can make the prepared hydrogel have excellent electrical conductivity and mechanical strength.
[0017] Furthermore, the preparation process of the aqueous solution of the polymer is: adding 0.1~1 g of polyvinyl alcohol into 10~50 mL of water, and then stirring at 50~100°C to dissolve it to obtain the aqueous solution of polyvinyl alcohol, which can make the gel form a double network structure, one layer of the network is betaine acrylic acid, and the other layer of the network is polyvinyl alcohol.
[0018] Furthermore, the ratio of acrylic acid, sulfobetaine, NN methylenebisacrylamide and initiator is (1-3) mL: (0.1-2) g: (0.01-0.05) g: (0.01-0.1) g, which can make the degree of gel cross-linking appropriate and achieve optimal mechanical strength.
[0019] Furthermore, NN methylenebisacrylamide is added to the monomer mixture, and after stirring for 1 to 2 hours, an initiator is added, and stirring is continued for 10 to 60 minutes, so that the persulfate ions in the initiator can effectively induce the polymer to start crosslinking.
[0020] Furthermore, during the thermal polymerization process, the temperature is 40-60° C. and the time is 3-6 h, which can effectively catalyze the polymerization of polymer chains.
[0021] Furthermore, the concentration of the ionic solution is 0.1-3 M, and the zwitterionic gel is immersed in the ionic solution for 1-2 days, so that the zinc ions in the ionic solution can be cross-linked with the gel, and the sulfate ions can toughen the PVA chains through the Hofmeister effect.
[0022] Furthermore, the concentration of the potassium hydroxide solution is 3-6 M, and the swelling treatment time is 1-2 days, which can make the gel swell and fully absorb the potassium hydroxide electrolyte to adapt to the zinc-air battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 The conductivity bar graph of the zwitterion-based gel electrolyte prepared in Examples 1 to 3 of the present invention; Figure 2 Graphs showing stress-strain curves of zwitterion-based gel electrolytes prepared in Examples 1 to 3 of the present invention; Figure 3 This is a scanning electron microscope image of the zwitterion-based gel electrolyte prepared in Example 2 of the present invention; Figure 4 This is an open circuit voltage diagram of a flexible zinc-air battery assembled using the zwitterion-based gel electrolyte prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The present invention provides a method for preparing a zwitterion-based gel electrolyte, comprising the following steps: S1: adding 0.1-1 g of a polymer to 10-50 mL of water, and then stirring at 50-100° C. to dissolve the polymer to obtain an aqueous solution of the polymer; dissolving acrylic acid and sulfobetaine in the aqueous solution of the polymer, and stirring to obtain a monomer mixture; The ratio of acrylic acid, sulfobetaine and high molecular polymer is (1-3) mL: (0.1-2) g: (0.1-1) g. The ratio of acrylic acid, sulfobetaine, NN methylenebisacrylamide and initiator is (1-3) mL: (0.1-2) g: (0.01-0.05) g: (0.01-0.1) g.
[0031] The high molecular polymer is at least one of polyvinyl alcohol, polyacrylamide and sodium polyacrylate; S2: adding NN methylenebisacrylamide to the monomer mixture, stirring for 1-2 h, adding an initiator, continuing to stir the reaction for 10-60 min, and then placing the product at 40-60 °C for thermal polymerization for 3-6 h to obtain a zwitterionic gel; Among them, NN methylenebisacrylamide is used as a cross-linking agent.
[0032] The initiator is ammonium persulfate or potassium persulfate.
[0033] S3: Soaking the zwitterion gel in a 0.1-3 M (ie, mol / L) ion solution for 1-2 days, and swelling the product in a 3-6 M potassium hydroxide solution for 1-2 days to obtain the zwitterion-based gel electrolyte.
[0034] The ion solution is at least one of zinc sulfate solution, sodium sulfate and sodium citrate.
[0035] In addition, the present invention also discloses a zwitterion-based gel electrolyte prepared by the above method, and a zinc-air battery containing the zwitterion-based gel electrolyte.
[0036] The ionic conductivity of the amphoteric ion-based gel electrolyte is 250-310 mS / cm, the tensile strength is 20-50 kPa, and the open circuit voltage of the zinc-air battery is 1.40-1.43 V.
[0037] Among them, the test process of ionic conductivity is: The ionic conductivity was calculated by electrochemical impedance spectroscopy. The electrochemical impedance spectroscopy was performed by an electrochemical workstation (CH760E, Shanghai Chenhua Instruments) with a frequency range of 100kHz to 0.1Hz and a voltage amplitude of 5mV. The solid electrolyte was clamped by two stainless steel sheets to measure the electrochemical impedance and obtain the electrochemical impedance spectrum. The conductivity calculation formula is as follows:
[0038] in d and A represent the thickness and surface area of the electrolyte, respectively. R b Represents the electrolyte volume resistance associated with the intersection of the X-axis in the electrochemical impedance spectrum.
[0039] The test process of tensile strength is: The mechanical properties of the gel electrolyte were studied by tensile testing the samples. The tensile rate was set at 10 mm / min until the sample was broken. The test process of open circuit voltage is: The gel was used to assemble a zinc-air battery, and the open circuit voltage was measured by an electrochemical workstation during operation.
[0040] The present invention utilizes the zwitterionic groups of sulfobetaine to form ion channels, and introduces polyvinyl alcohol as the second network to enhance the mechanical properties of the gel through the Hofmeister effect. The honeycomb pore structure finally formed can absorb a large amount of electrolyte solution and has excellent hydration. Finally, an excellent gel electrolyte material is obtained. - Polar groups and -SO3 - The zinc affinity of the group on the Zn anode inhibits the formation of Zn dendrites. - The strong hydrogen bonds between the groups and water molecules and the electrostatically induced hydration of the zwitterionic groups can prevent the gel electrolyte from freezing at low temperatures and evaporating at high temperatures, thereby increasing the operating temperature range of the battery.
[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0042] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0043] Example 1 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: a. Use an electronic balance to weigh 0.1 g of polyvinyl alcohol, dissolve it in 10 mL of deionized water, place it in an oil bath at 95 °C and stir it thoroughly to dissolve it. This is recorded as solution A.
[0044] b. Dissolve 2 mL of acrylic acid and 0.5 g of sulfobetaine in solution A and stir thoroughly to mix them evenly. This is called solution B.
[0045] c. Add 0.01 g N-N methylenebisacrylamide NN methylenebisacrylamide to B while stirring, and stir for 1 h. Then add 0.05 g ammonium persulfate, continue stirring for 10 min, and then place in a 60 °C oven for polymerization for 3 h to form a gel.
[0046] d. Soak the polymerized gel in a 2 M zinc sulfate solution for 2 days, then place the soaked gel in a 6 M potassium hydroxide solution to swell, and finally form a solid electrolyte.
[0047] Example 2 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: a. Use an electronic balance to weigh 0.1 g of polyvinyl alcohol, dissolve it in 10 mL of deionized water, place it in an oil bath at 95 °C and stir it thoroughly to dissolve it. This is recorded as solution A.
[0048] b. Dissolve 2 mL of acrylic acid and 1 g of sulfobetaine in solution A and stir thoroughly to mix them evenly. This is called solution B.
[0049] c. Add 0.01 g N-N methylenebisacrylamide NN methylenebisacrylamide to B while stirring, and stir for 1 h. Then add 0.05 g ammonium persulfate, continue stirring for 10 min, and then place in a 60 °C oven for polymerization for 3 h to form a gel.
[0050] d. Soak the polymerized gel in a 2 M zinc sulfate solution for 2 days, then place the soaked gel in a 6 M potassium hydroxide solution to swell, and finally form a solid electrolyte.
[0051] Example 3 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: a. Use an electronic balance to weigh 0.1 g of polyvinyl alcohol, dissolve it in 10 mL of deionized water, place it in an oil bath at 95 °C and stir it thoroughly to dissolve it. This is recorded as solution A.
[0052] b. Dissolve 2 mL of acrylic acid and 1.5 g of sulfobetaine in solution A and stir thoroughly to mix them evenly. This is called solution B.
[0053] c. Add 0.01 g N-N methylenebisacrylamide NN methylenebisacrylamide to B while stirring, and stir for 1 h. Then add 0.05 g ammonium persulfate, continue stirring for 10 min, and then place in a 60 °C oven for polymerization for 3 h to form a gel.
[0054] d. Soak the polymerized gel in a 2 M zinc sulfate solution for 2 days, then place the soaked gel in a 6 M potassium hydroxide solution to swell, and finally form a solid electrolyte.
[0055] Example 4 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: S1: adding 0.1 g of polyvinyl alcohol to 10 mL of water, and then stirring at 50° C. to dissolve it, to obtain an aqueous solution of the polyvinyl alcohol; dissolving acrylic acid and sulfobetaine in the aqueous solution of the polyvinyl alcohol, and stirring to obtain a monomer mixture; The ratio of acrylic acid, sulfobetaine and polyvinyl alcohol is 1 mL:0.1 g:0.1 g.
[0056] S2: adding NN methylenebisacrylamide as a crosslinking agent to the monomer mixture, stirring for 1 h, adding ammonium persulfate, continuing to stir and react for 10 min, and then placing the product at 40 ° C for 6 h for thermal polymerization to obtain a zwitterionic gel; The ratio of acrylic acid, sulfobetaine, NN methylenebisacrylamide and ammonium persulfate is 1 mL: 0.1 g: 0.01 g: 0.01 g.
[0057] S3: The zwitterion gel is immersed in a 0.1 M zinc sulfate solution for 1 day, and the product is placed in a 3 M potassium hydroxide solution for swelling treatment for 1 day to obtain the zwitterion-based gel electrolyte.
[0058] In addition, the present invention also discloses a zwitterion-based gel electrolyte prepared by the above method, and a zinc-air battery containing the zwitterion-based gel electrolyte.
[0059] The ionic conductivity of the zwitterionic gel electrolyte is 250 mS / cm, the tensile strength is 20 kPa, and the open circuit voltage of the zinc-air battery is 1.40 V.
[0060] Example 5 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: S1: 1 g of polyacrylamide is added to 50 mL of water, and then stirred at 100°C to dissolve it, to obtain an aqueous solution of the polyacrylamide; acrylic acid and sulfobetaine are dissolved in the aqueous solution of polyacrylamide, and stirred to obtain a monomer mixture; The ratio of acrylic acid, sulfobetaine and polyacrylamide is 3mL:2g:1g.
[0061] S2: adding NN methylenebisacrylamide as a crosslinking agent to the monomer mixture, stirring for 2 h, adding potassium persulfate, continuing to stir and react for 60 min, and then placing the product at 60 ° C for thermal polymerization for 3 h to obtain a zwitterionic gel; The ratio of the acrylic acid, sulfobetaine, NN methylenebisacrylamide and potassium persulfate is 3mL:2g:0.05g:0.1g.
[0062] S3: Soaking the zwitterion gel in 3 M sodium sulfate for 2 days, and placing the product in 6 M potassium hydroxide solution for swelling treatment for 2 days to obtain the zwitterion-based gel electrolyte.
[0063] In addition, the present invention also discloses a zwitterion-based gel electrolyte prepared by the above method, and a zinc-air battery containing the zwitterion-based gel electrolyte.
[0064] The ionic conductivity of the zwitterionic gel electrolyte is 310 mS / cm, the tensile strength is 50 kPa, and the open circuit voltage of the zinc-air battery is 1.43 V.
[0065] Example 6 A method for preparing a zwitterion-based gel electrolyte comprises the following steps: S1: adding 0.5 g of sodium polyacrylate to 30 mL of water, and then stirring at 80° C. to dissolve it, to obtain an aqueous solution of the sodium polyacrylate; dissolving acrylic acid and sulfobetaine in the aqueous solution of sodium polyacrylate, and stirring to obtain a monomer mixture; The ratio of acrylic acid, sulfobetaine and sodium polyacrylate is 2mL:1g:0.5g.
[0066] S2: adding NN methylenebisacrylamide as a crosslinking agent to the monomer mixture, stirring for 1.5 h, adding ammonium persulfate, continuing to stir and react for 30 min, and then placing the product at 50 ° C for 5 h for thermal polymerization to obtain a zwitterionic gel; The ratio of the acrylic acid, sulfobetaine, NN methylenebisacrylamide and ammonium persulfate is 2mL:1g:0.02g:0.05g.
[0067] S3: The zwitterion gel is immersed in 2 M sodium citrate for 1.5 days, and the product is placed in 4 M potassium hydroxide solution for swelling treatment for 1.5 days to obtain the zwitterion-based gel electrolyte.
[0068] In addition, the present invention also discloses a zwitterion-based gel electrolyte prepared by the above method, and a zinc-air battery containing the zwitterion-based gel electrolyte.
[0069] The ionic conductivity of the zwitterionic gel electrolyte is 300 mS / cm, the tensile strength is 30 kPa, and the open circuit voltage of the zinc-air battery is 1.41 V.
[0070] Figure 1 The conductivity bar graph of the zwitterion-based gel electrolytes prepared in Examples 1 to 3 of the present invention is shown. As can be seen from the graph, the zwitterion-based gel electrolytes prepared in the present invention have a relatively high conductivity, which can reach up to 304 mS / cm.
[0071] Figure 2 The stress-strain curves of the zwitterion-based gel electrolytes prepared in Examples 1 to 3 of the present invention are as follows. It can be seen from the figure that the zwitterion-based gel electrolytes prepared in the present invention have good tensile capacity and can meet the general application scenarios of solid-state zinc-air batteries.
[0072] FIG3 is an electron microscope scanning image of the zwitterion-based gel electrolyte prepared in Example 2 of the present invention. As can be seen from the figure, the zwitterion-based gel electrolyte prepared in the present invention has a uniform porous structure, which is conducive to the transmission of ions in the solid electrolyte and effectively improves the ionic conductivity.
[0073] FIG4 is an open circuit voltage diagram of a flexible zinc-air battery assembled using the zwitterion-based gel electrolyte prepared in Example 2 of the present invention. The open circuit voltage is an important indicator of battery performance, and its level reflects the potential difference between the positive and negative electrodes of the battery in the open circuit state (i.e., when the battery is not connected to the circuit and no current passes). A high open circuit voltage means that during the discharge of the battery, chemical energy can be more effectively converted into electrical energy, thereby improving the energy conversion efficiency of the battery. At the same time, under the same conditions, a battery with a high open circuit voltage can provide a higher output power and meet application scenarios with higher energy requirements. In addition, the zwitterion-based gel electrolyte has a higher ion conductivity and can more effectively promote the migration and diffusion of ions inside the battery, thereby increasing the open circuit voltage of the battery. The gel electrolyte may have a more stable three-dimensional network structure, which can maintain good stability and mechanical strength during the battery charge and discharge process, thereby supporting a higher open circuit voltage. As can be seen from the figure, the open circuit voltage of the flexible zinc-air battery assembled using the zwitterion-based gel electrolyte prepared by the present invention is as high as 1.428V, which is much higher than the common PVA gel electrolyte.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a zwitterion-based gel electrolyte, characterized in that: The following steps are involved: S1: dissolving acrylic acid and sulfobetaine in an aqueous solution of a high molecular weight polymer, and stirring to obtain a monomer mixture; the high molecular weight polymer is at least one of polyvinyl alcohol, polyacrylamide and sodium polyacrylate; S2: adding NN methylenebisacrylamide to the monomer mixture, stirring evenly, adding an initiator, continuing to stir for reaction, and then thermally polymerizing the product to obtain a zwitterionic gel; S3: After the zwitterion gel is immersed in an ion solution, the product is placed in a potassium hydroxide solution for swelling treatment to obtain the zwitterion-based gel electrolyte; the ion solution is at least one of zinc sulfate solution, sodium sulfate and sodium citrate.
2. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: The ratio of the acrylic acid, sulfobetaine and high molecular polymer is (1-3) mL: (0.1-2) g: (0.1-1) g.
3. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: The preparation process of the aqueous solution of the polymer is as follows: 0.1-1 g of the polymer is added into 10-50 mL of water, and then stirred at 50-100° C. to dissolve the polymer, thereby obtaining the aqueous solution of the polymer.
4. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: The ratio of the acrylic acid, sulfobetaine, NN methylenebisacrylamide and initiator is (1-3) mL: (0.1-2) g: (0.01-0.05) g: (0.01-0.1) g.
5. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: Add NN methylenebisacrylamide to the monomer mixture, stir for 1 to 2 hours, then add the initiator and continue stirring for 10 to 60 minutes.
6. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: During the thermal polymerization process, the temperature is 40-60°C and the time is 3-6 hours.
7. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: The concentration of the ionic solution is 0.1-3 M, and the zwitterionic gel is immersed in the ionic solution for 1-2 days.
8. The method for preparing a zwitterion-based gel electrolyte according to claim 1, characterized in that: The concentration of the potassium hydroxide solution is 3-6 M, and the swelling treatment time is 1-2 days.
9. A zwitterion-based gel electrolyte, characterized in that: The method is prepared by the method according to any one of claims 1 to 8; the ionic conductivity of the zwitterionic gel electrolyte is 250 to 310 mS / cm; and the tensile strength is 20 to 50 kPa.
10. A zinc-air battery, characterized in that: The invention comprises a zwitterion-based gel electrolyte as claimed in claim 9; the open circuit voltage of the zinc-air battery is 1.40-1.43V.
Citation Information
Patent Citations
Preparation method and application of double-network polyvinyl alcohol-polyacrylic acid hydrogel
CN113174062A
Zwitterionic organogel electrolyte, preparation method thereof and application of zwitterionic organogel electrolyte in supercapacitor
CN114621396A
Ampholytic polymer capable of absorbing aqueous electrolyte solution
US5512644A
Cited By
Porous composite gel as well as preparation method and application thereof in atmospheric catchment
CN121005949A